Relation between the energy. Gap and ultrasonic wave propagation velocities in semiconductors - OPILSKA, L.; OPILSKI, A.; LATACZ, Z. (Archives of Acoustics, 1980)
In this work the existence of the relation between the energy gap and ultrasonic wave velocities for semiconductors crystallizing into cubic and hexagonal systems has been shown. Data from the literature confirmed the validity of the relations obtained. Using the acoustical method the variation of the energy gap with the percentage composition of the solid solutions has also been obtained.